Dimensi Sosial Ibadah Sholat dalam Perspektif Hadis: Upaya Membangun Solidaritas dan Ukhwah Islamiyyah - Rafi Saifullah; Deri Hermawan; Inong Satriadi (YASIN, 2026)
Although the practice of ritual prayer has been extensively discussed in Islamic studies, research that specifically examines the social dimension of prayer from a hadith perspective as a means of fostering solidarity and ukhuwah Islamiyyah remains relatively limited. This study aimed to analyze and describe the social dimension of prayer based on the hadiths of the Prophet Muhammad and its implications for strengthening solidarity and brotherhood among Muslims. A qualitative approach was employed using a library research design grounded in thematic hadith analysis. The data consisted of authentic hadiths related to prayer, particularly congregational prayer, collected from major hadith compilations and classical and contemporary hadith commentaries. These data were gathered through documentation techniques and analyzed thematically to identify the social values embedded within them. The findings indicate that prayer, especially congregational prayer, possesses a strong social dimension in cultivating collective awareness, social equality, shared discipline, empathy, and mutual care among Muslims. Hadiths on the virtues of congregational prayer, the command to straighten and close the rows, and the parable of believers as one body affirm the function of prayer as a collective ritual that reinforces social solidarity and ukhuwah Islamiyyah. These results demonstrate that prayer is not solely oriented toward individual piety but also plays a strategic role in shaping social piety. The study concludes by underscoring the importance of a comprehensive understanding and practice of prayer as an instrument for nurturing harmonious social relations, while offering theoretical contributions to the development of interdisciplinary hadith studies and practical implications for Islamic religious and educational institutions in strengthening solidarity and ukhuwah Islamiyyah.